Linkages Between Patient-centered Medical Homes and Addiction Treatment Organizations: Results From a National Survey. Issue 4 (April 2017) - D'Aunno, Thomas; Pollack, Harold; Chen, Qixuan; Friedmann, Peter D.
Abstract : Background: To meet their aims of providing comprehensive and coordinated care, patient-centered medical homes (PCMHs) need to coordinate services for individuals with substance use disorders. Yet, the 14, 000 addiction treatment (AT) organizations across the United States that provide services for more than 1 million individuals daily are generally ill-prepared to work with PCMHs (eg, AT organizations often lack electronic health records). Objectives: To examine the extent to which AT organizations have formal linkages through contracts with PCMHs; to identify key dimensions of linkages between PCMHs and AT organizations (eg, shared use of electronic health records); to identify characteristics of AT organizations and their environments associated with these linkages. Materials and Methods: We draw on data from a 2014 nationally representative survey of directors and clinical supervisors from 695 AT organizations (n=1390 survey respondents). Results: Thirty-eight percent of patients across the nation are receiving treatment in AT organizations linked by contracts to PCMHs. This number increases to 51% in states that expanded Medicaid (vs. only 6.2% of patients in non-Medicaid expansion states). Yet, the great majority of linkages are relatively weak; they do not include the exchange of patient information. Results from multivariable analyses show that larger, nonprofit and publicly owned AT organizations, as well as those located in the northeast and in states that expanded Medicaid coverage, are more likely to have contracts with PCMHs. Conclusions: Without stronger linkages between AT organizations and PCMHs or the development of other models that integrate services, individuals with substance abuse disorders may continue to receive uncoordinated care. Abstract : Supplemental Digital Content is available in the text.